Partisipasi Mahasiswa Kuliah Kerja Nyata dalam Kegiatan Mengajar Sekolah Dasar di Desa Sumberagung Kabupaten Nganjuk - Rinda Purwati; Merlina Aris; Yemima Dya Novitasari; Hendra Maulana (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Community Service Program (KKN) is a part of educational activities as well as devotion to the community which is a learning tool for students to actively contribute to society and help solve the problems faced. Participation is independent participation or active initiative in various activities and situations within a group or society. The participation of KKN students in the community is shown in teaching activities conducted at SDN 1 Sumberagung. The implementation of this teaching activity is done using question-and-answer learning methods to encourage students and students to understand the material submitted, and train to express their opinions. The use of audio, visual, and audiovisual learning media is also done by KKN students so that students can feel a new atmosphere and learning activities are getting interesting.